Hypothalamic Transcriptome Analysis Reveals the Crucial MicroRNAs and mRNAs Affecting Litter Size in Goats - Liang, Chen; Han, Miaoceng; Zhou, Zuyang; Liu, Yufang; He, Xiaoyun; Jiang, Yanting; Ouyang, Yina; Hong, Qionghua; Chu, Mingxing (Frontiers in Veterinary Science, 2021)
The hypothalamus was the coordination center of the endocrine system, which played an important role in goat reproduction. However, the molecular mechanism of hypothalamus regulating litter size in goats was still poorly understood. This study aims to investigate the key functional genes associated with prolificacy by hypothalamus transcriptome analysis of goats. In this research, an integrated analysis of microRNAs (miRNAs)-mRNA was conducted using the hypothalamic tissue of Yunshang black goats in the follicular stage. A total of 72,220 transcripts were detected in RNA-seq. Besides, 1,836 differentially expressed genes (DEGs) were identified between high fecundity goats at the follicular phase (FP-HY) and low fecundity goats at the follicular phase (FP-LY). DEGs were significantly enriched in 71 Gene Ontology (GO) terms and 8 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. The transcriptome data suggested that DEGs such as BMPR1B, FGFR1, IGF1 and CREB1 are directly or indirectly involved in many processes like hypothalamic gonadal hormone secretion. The miRNA-seq identified 1,837 miRNAs, of which 28 differentially expressed miRNAs (DEMs). These DEMs may affect the nerve cells survival of goat hypothalamic regulating the function of target genes and further affect the hormone secretion activities related to reproduction. They were enriched in prolactin signaling pathway, Jak-STAT signaling pathway and GnRH signaling pathway, as well as various metabolic pathways. Integrated analysis of DEMs and DEGs showed that 87 DEGs were potential target genes of 28 DEMs. After constructing a miRNA-mRNA pathway network, we identified several mRNA-miRNAs pairs by functional enrichment analysis, which was involved in hypothalamic nerve apoptosis. For example, NTRK3 was co-regulated by Novel-1187 and Novel-566, as well as another target PPP1R13L regulated by Novel-566. These results indicated that these key genes and miRNAs may play an important role in the development of goat hypothalamus and represent candidate targets for further research. This study provides a basis for further explanation of the basic molecular mechanism of hypothalamus, but also provides a new idea for a comprehensive understanding of prolificacy characteristics in Yunshang black goats.